Central Blood Pressure and Vascular Aging in Patients with Type 2 Diabetes Mellitus - Emil Fraenkel; Ioana Mozos (Artery Research)
Abstract Background Structural modifications of conduit arteries in diabetes mellitus substantially contribute to subclinical changes including increased arterial stiffness, which is recognized as one of the dominant hemodynamic manifestations of vascular aging, and a determinant of central systolic blood pressure (cSBP). However, it remains unclear whether elevated cSBP might be an independent contributor to arterial stiffness. The present study aimed to evaluate the contribution of central blood pressure calculated via an Arteriograph (TensioMed, Hungary) to the identification of patients with impaired vascular function. Methods This observational cross-sectional study included 125 obese/overweight patients aged 22–72 years, with type 2 diabetes mellitus (T2DM), on antidiabetic medication. Patients may have hypertension as a concomitant disease. Pulse wave analysis was conducted via an Arteriograph. Correlation analysis was performed between the brachial augmentation index (AIx), pulse wave velocity (PWV), cSBP, systolic (SBP), diastolic BP (DBP), and central aortic pulse pressure (cPP). In the case of significant partial correlation coefficients and after the exclusion of multicollinearity, multiple linear regression was performed, adjusted for age, heart rate and height. According to these models, ROC curves were prepared with cutoff values of PP = 60 mmHg used as classifiers of impaired vascular function. Results The values of the evaluated parameters were, as follows: AIx -23.6 ± 32.7%, PWV 9.1±2.3 m/s, cSBP 127.4± 21.7 mmHg, SBP 133.1± 18.5 mmHg, DBP 80.9± 10.5 mmHg, and cPP 49.97 ± 12.9 mmHg. Significant correlations were obtained between cSBP and AIx (r = 0.65, p<0.05), cSBP and PWV (r = 0.48, p<0.05), PWV and AIx (r = 0.50, p<0.05), and cPP and cSBP (r = 0.75, p<0.05). Significant models were obtained for PWV with PP = 60 mmHg as a classifier: cSBP and age (AUROC = 0.824 (R2 = 0.28, p<0.05)); for AIx with PP = 60 mmHg as a classifier: cSBP and age (AUROC = 0.773 (R2 = 0.44, p<0.05)); cSBP, age and height (AUROC = 0.776 (R2 = 0.53, p<0.05); cSBP, age and heart rate (AUROC = 0.699 (R2 = 0.59, p<0.05); cSBP, age, height and heart rate (AUROC = 0.658 (R2 = 0.70, p<0.05). Conclusion Our results revealed strong correlations between cSBP and other measures of vascular function assessed by the Arteriograph. Our models demonstrated that cSBP determined by the Arteriograph is identifying patients with arterial stiffening independently of potential confounders, and, therefore, the Arteriograph may serve as a screening tool for patients with diabetes mellitus.